DETERMINANTS OF GREEN MARKETING QUALITY PRACTICES AMONG SMALL MEDIUM ENTERPRISES (SMEs) - Wiwiek Rabiatul Adawiyah (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2017)
The phenomenon of green marketing practices is growing in popularity. People are becoming more sensitive towards environmental issue which is a favorable social consciousness. Considering substantial numbers of small and medium enterprises (SMEs) operating in Indonesia, there is a need for assessing the environmental impacts of their operations. The study aims at determining the antecedents of green marketing quality practices among SMEs. The sample of study was export-oriented SMEs located in Banyumas Regency Central Java Indonesia. One hundred and twenty-five companies were selected as the respondents of the study. Data were gathered using questionnaire containing items measured using Likert scale. Data were analyzed using multiple linear regressions, and the finding showed that all independent variables except environmental consciousness have significant influence on green marketing quality practice by SMEs. The most influential factor on marketing quality of SMEs was social impressions. The implication of the study is that every SME should always put their best effort in preventing environmental damaged resulting from companies’ operation. Location in where sample was selected was conveniently determined (convenient sampling). Including other provinces as research locations might improve the representativeness of the data, and might ultimately give different result on this area of study.